Prevalence of Pyromaniac Disorder in Adolescents - Jarwan, Ali Saleh; Bani Mustafa, Manar Saeed (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed at identifying the prevalence of pyromania disorder among adolescents according to their school stage, academic achievement, and place of residence. Methods: A pyromania disorder scale consisting of (10) items was developed. After testing the validity and reliability indicators of the scale, it was applied to (1027) adolescents in primary and secondary school stages in the governorates of Jerash and Ajloun, who were selected by the available method. Results: The study results indicate that the prevalence of pyromania disorder among adolescents was (15.6%). There was a significant difference in the prevalence of pyromania disorder among adolescents related to their place of residence, with a higher prevalence in favor of the village. However, there were no significant differences concerning the variables of school stage and/or academic achievement. Conclusions: The study recommends organizing seminars and lectures to increase awareness among adolescents about pyromania disorder and its negative effects on both individual and societal levels.